Det hebræiske bibeloversættelsesprojekt - Herbener, Jean-André P. (Religionsvidenskabeligt Tidsskrift, 2002)
The guidelines of a planned translation of the Hebrew Bible into Danish and as an annotated sample translation of selected texts were published in Denmark last year. The work is based on a pilot project initiated in 1998 and completed in 2001. It is the intention that a retranslation of the Hebrew Bible will be published continously the following nine years, divided in eight annotated publications with a translation of the Pentateuch being the first. The purpose of The Hebrew Bible Translation Project is to work out a Danish translation of the Hebrew Bible on a scholarly and secular foundation. This article presents what this purpose implies, and it discusses some of the methodical and hermeneutical considerations constituting the basis of the translation, as compared with other Biblie translations. According to the publishers a secular scholarly translation implies that the Hebrew Bible texts must be reproduced in accordance with the geographical, historical and religious context in which they were written, and that no consideration must be taken of the historical effects of the text in post-biblical traditions or, consequently, to the perception and usage of the texts by modern religious communities. In this respect, the new project differs not only from the older, but also from the majority of modern Bible translations, based on a mixture between strictly scholarly and traditional/confessional considerations.